Enhancing physical activity knowledge exchange strategies for Canadian long-haul truck drivers. Issue 2 (11th April 2020) - Gorczynski, Paul F.; Edmunds, Sarah; Lowry, Ruth
Abstract : Purpose: Canadian long-haul truck drivers lead sedentary lives, but are receptive to receiving physical activity information to address health risks. This study examined how Canadian long-haul truck drivers would like to receive physical activity information in order to improve their overall health. The purpose of this study was twofold: 1) explore barriers Canadian long-haul truck drivers have to receiving and using physical activity information and 2) understand how physical activity information should be structured and delivered to these drivers to overcome these barriers. Design/methodology/approach: Semi-structured interviews were conducted with 12 Canadian long-haul truck drivers. Drivers had, on average, 14.3 years of professional long-haul driving experience. Findings: Few drivers had received any physical activity information. Drivers discussed a culture where they perceived both employers and drivers to be lacking awareness of the importance of physical activity and its impact on health. Drivers explained they were too busy, stressed or tired to be active or to learn about physical activity. Information received by some drivers on this topic was too general to be helpful in changing physical activity behaviours. Drivers mentioned that personalized and accessible physical activity information should be provided to them through multiple methods by their employers, as an aspect of occupational health and safety. Practical implications: Future physical activity information strategies should use both passive and interactive mediums to promote physical activity to Canadian long-haul truck drivers. Originality/value: This is the first study to assess how Canadian long-haul truck drivers would like to receive trustworthy information that can lead to healthful improvements in physical activity behaviour.